Insufficient sleep is associated with a pro‐atherogenic circulating microRNA signature - Hijmans, Jamie G.; Levy, Ma'ayan; Garcia, Vinicius; Lincenberg, Grace M.; Diehl, Kyle J.; Greiner, Jared J.; Stauffer, Brian L.; DeSouza, Christopher A. (Experimental physiology, 2019)
New Findings What is the central question of the study Is habitual short sleep associated with altered circulating levels of specific inflammation‐ and vascular‐related microRNAs? What is the main finding and its importance? Circulating levels of miR‐125a, miR‐126 and miR‐146a were significantly lower in the short sleep compared with the normal sleep group. Altered circulating profiles of these vascular‐related microRNAs have been linked to vascular inflammation, dysfunction and increased cardiovascular disease events. Sleep‐related changes in these microRNAs are consistent with, and might play a role in, the aberrant vascular physiology and increased vascular risk associated with short sleep. Habitual short sleep duration (<7 h night−1) is associated with increased morbidity and mortality attributable, in large part, to increased inflammatory burden and endothelial dysfunction. MicroRNAs (miRNAs) play a key role in regulating vascular health, and circulating levels are now recognized to be sensitive and specific biomarkers of cardiovascular function, inflammation and disease.  The aim of this study was to determine whether the expression of circulating miR‐34a, miR‐92a, miR‐125a, miR‐126, miR‐145, miR‐146a and miR‐150 is disrupted in adults who habitually sleep <7 h night−1 (short sleep). These were chosen based upon their well‐established links with vascular inflammation, function and, in turn, cardiovascular risk. Twenty‐four adults were studied: 12 with normal nightly sleep duration (six men and six women; age, 55 ± 3 years old; sleep duration, ≥7.0 h night−1) and 12 with short nightly sleep duration (seven men and five women; 55 ± 2 years old; sleep duration, <7 h night−1), and circulating miRNA expression was assayed by RT‐PCR. All subjects were non‐smokers, normolipidaemic, non‐medicated and free of overt cardiovascular disease. Circulating levels of miR‐125a (3.07 ± 1.98 versus 7.34 ± 5.34 a.u.), miR‐126 [1.28 (0.42–2.51) versus 1.78 (1.29–4.80) a.u.] and miR‐146a [2.55 (1.00–4.80) versus 6.46 (1.50–11.44) a.u.] were significantly lower (∼60, 40 and 60%, respectively) in the short compared with the normal sleep group. However, there were no significant group differences in circulating levels of miR‐34a, miR‐92a, miR‐145 and miR‐150. In summary, chronic short sleep is associated with a marked reduction in circulating levels of miR‐125a, miR‐126 and miR‐146a. Dysregulation of these miRNAs might contribute to the increased inflammatory burden and endothelial dysfunction associated with habitual insufficient sleep.